Mothers’ Handwashing Knowledge as a Predictor of Diarrheal Disease Among Under-Five Children Visiting Pediatric Ward in University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2019 - Andualem Z; Dagne H; Taddese AA; Dagnew B (Dove Medical Press, 2019)
Zewudu Andualem,1 Henok Dagne,1 Asefa Adimasu Taddese,2 Baye Dagnew3 1Department of Environmental and Occupational Health and Safety, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Human Physiology, Sciences School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Zewudu Andualem; Henok DagneDepartment of Environmental and Occupational Health and Safety, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaEmail zewuduandualem12@gmail.com; enoch2313@gmail.comBackground: Diarrheal disease is one of the leading causes of mortality and morbidity among under-five children in the world and often results from contaminated food and water. The aim of this study was to assess the prevalence of diarrheal disease among under-five children visiting the pediatric ward in University of Gondar Comprehensive Specialized Hospital and its association with their mothers’ handwashing knowledge.Methods: An institutional-based cross-sectional study was conducted from May to July 2019 among under-five children visiting the pediatric ward in University of Gondar Comprehensive Specialized Hospital. An interviewer-administered questionnaire was used to collect the data. Chart review was undertaken using a data abstraction form. A simple random sampling technique was used to select the study participants. Data were entered using Epi Info version 7 and analyzed using STATA version 14.0. A binary logistic regression analysis was employed between dependent and independent variables to determine association. The statistical significance was declared at P<0.05.Results: In this study, the prevalence of diarrheal disease among under-five children visiting the pediatric ward in University of Gondar Comprehensive Specialized Hospital was 30.09% (95% CI: (26%, 35%)). Age of mothers (AOR=3.72, 95% CI: (1.67, 8.28)), mothers’ educational status (AOR=0.44, 95% CI: (0.23, 0.80)), malnutrition (AOR=6.72, 95% CI: (3.44, 13.11)), and maternal knowledge of handwashing (AOR=0.49, 95% CI: (0.27, 0.90)) were factors associated with diarrheal disease among under-five children.Conclusion: The prevalence of diarrheal disease was higher in the current study, which is a major public health concern. Age of mothers, malnutrition, and mothers’ handwashing knowledge and educational status were significantly associated with diarrheal disease of under-five children. In order to reduce diarrheal disease and improve child health, attention should be given to improving mothers’ educational status and knowledge regarding handwashing.Keywords: diarrheal disease, knowledge, under-five children